2018
DOI: 10.2147/ott.s167780
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression analyses identify a relationship between stanniocalcin 2 and the malignant behavior of colorectal cancer

Abstract: BackgroundColorectal cancer (CRC) is one of the main causes of cancer-related death worldwide. Stanniocalcin 2 (STC2), a secreted glycoprotein, has been suggested to exert various functions in progression of many cancers. However, the precise biological role in CRC is not fully understood. Therefore, this study based on several public datasets aims at investigating the roles of STC2 in CRC.MethodsWe used The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) databases to evaluate the STC2 expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…For example, Yang et al [32] suggested that high expression of STC2 promotes the migration and invasion of head and neck squamous cell carcinoma cells in vitro and in vivo through the PI3K/AKT pathway may. Wang et al [33] speculated that STC2 promoted lymphatic metastasis through VEGF-C/VEGF-D/VEGFR-3 pathway and EMT-related molecules in colorectal cancer. One study elaborated that STC2 contributes to hepatocellular carcinoma progression and metastasis by affecting cells viability, colony formation, and migration ability in a dominant-positive manner.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Yang et al [32] suggested that high expression of STC2 promotes the migration and invasion of head and neck squamous cell carcinoma cells in vitro and in vivo through the PI3K/AKT pathway may. Wang et al [33] speculated that STC2 promoted lymphatic metastasis through VEGF-C/VEGF-D/VEGFR-3 pathway and EMT-related molecules in colorectal cancer. One study elaborated that STC2 contributes to hepatocellular carcinoma progression and metastasis by affecting cells viability, colony formation, and migration ability in a dominant-positive manner.…”
Section: Discussionmentioning
confidence: 99%
“…45 Further investigations have shown that STC2 promotes epithelial-mesenchymal transition (EMT), migration, and chemoresistance in CRC, involving activation of the ERK/MEK and PI3K/ AKT signaling pathways. 45,46 In addition, STC2 has been associated with anti-VEGF resistance and chemoresistance to oxaliplatin. 47,48 These findings highlight the clinical significance of STC2 in CRC and its involvement in EMT and chemoresistance through multiple potential pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, elevated serum STC2 levels have been correlated with poor patient survival and pathological grade, suggesting the potential of STC2 as a serum biomarker 45 . Further investigations have shown that STC2 promotes epithelial–mesenchymal transition (EMT), migration, and chemoresistance in CRC, involving activation of the ERK/MEK and PI3K/AKT signaling pathways 45,46 . In addition, STC2 has been associated with anti‐VEGF resistance and chemoresistance to oxaliplatin 47,48 .…”
Section: Discussionmentioning
confidence: 99%
“…In colorectal cancer, CCDC85B (also known as DIPA) is a carcinogenetic gene (22). It could be found on the centrosome and directly interacts with p78 and influences malignant transformation by modulating gene transcription (23).…”
Section: Discussionmentioning
confidence: 99%